New naphthalene derivative for cost-effective AChE inhibitors for Alzheimer's treatment: In silico identification, in vitro and in vivo validation. (December 2020) - Anwar, Fareeha; Saleem, Uzma; Ahmad, Bashir; Ashraf, Muhammad; Rehman, Atta Ur; Froeyen, Matheus; Kee, Lee Yean; Abdullah, Iskandar; Mirza, Muhammad Usman; Ahmad, Sarfraz
Graphical abstract: Highlights: In silico tools including MD simulation and MMGBSA were used to identify two cost-effective compounds as AChE inhibitors. Selected compounds were also screened against BChE, LOX and α-glucosidase. Compound 3a significantly diminish AChE levels in the mice brain as compared to the control. Abstract: Neurodegenerative diseases have complex etiology and pose a challenge to scientists to develop simple and cost-effective synthetic compounds as potential drug candidates for such diseases. Here, we report an extension of our previously published in silico screening, where we selected four new compounds as AChE inhibitors. Further, based on favorable binding possess, MD simulation and MMGBSA, two most promising compounds (3a and 3b ) were selected, keeping in view the ease of synthesis and cost-effectiveness. Due to the critical role of BChE, LOX and α-glucosidase in neurodegeneration, the selected compounds were also screened against these enzymes. The IC50 values of 3a against AChE and BChE found to be 12.53 and 352.42 μM, respectively. Moderate to slight inhibitions of 45.26 % and 28.68 % were presented by 3a against LOX and α-glucosidase, respectively, at 0.5 mM. Insignificant inhibitions were observed with 3b against the four selected enzymes. Further, in vivo trial demonstrated that 3a could significantly diminish AChE levels in the mice brain as compared to the control. These findings were in agreement with the histopathological analysis of the brain tissues. The results corroborate that selected compounds could serve as a potential lead for further development and optimization as AChE inhibitors to achieve cost-effective anti-Alzheimer's drugs.